(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper proposes a new generalized and refined model for solar electric differential drive Mobile Robotic platforms (SEDDMRP) and some considerations regarding design, modeling and control solutions. The proposed system design consists of seven main subsystems, each subsystem, is mathematically described and corresponding Simulink sub-model is developed, then an integrated generalized overall model of all subsystems is developed. The proposed whole SEDDMRP system model is developed for research purposes and application in educational process, to help in facing the main challenges in developing Mechatronics SEV systems; early identifying system level problems and ensuring that all design requirements are met, also, it is developed to allow designer to have the maximum output data to select, evaluate and control the overall SEDDMRP system and each subsystem outputs characteristics and response, for desired overall and/or either subsystem’s specific outputs, under various PV subsystem input operating conditions, to meet particular SEDDMRP system requirements and performance. The obtained results show the simplicity, accuracy and applicability of the presented models in Mechatronics design of SEDDMRP system application.